The Spatial Relationship Characteristics and Differentiation Causes Between Traditional Villages and Intangible Cultural Heritage in China - Xinyan Qian; Yi Yu; Runjiao Liu (Buildings)
Traditional villages (TVs) and intangible cultural heritage (ICH) serve as dual carriers for the living transmission of agrarian civilization, with their spatial compatibility being crucial for the sustainable development of cultural ecosystems. Existing research shows deficiencies in quantitative analysis, multidimensional driving mechanism interpretation, and spatial heterogeneity identification. This study establishes a three-phase framework (“spatial pattern identification–spatial relationship analysis–impact mechanism assessment”) using nationwide data encompassing 8155 TVs and 3587 ICH elements. Through the comprehensive application of the spatial mismatch index, Optimal-Parameter Geographic Detector (OPGD), and multiscale geographically weighted regression (MGWR) model, we systematically reveal their spatial differentiation patterns and driving mechanisms. Key findings: First, TVs exhibit a “three-primary-core and two-secondary-core” strong agglomeration pattern, while ICH shows multi-center balanced distribution. Significant positive spatial correlation coexists with prevalent mismatch: 65% of China’s territory displays positive mismatch (ICH dominance) and 35% displays negative mismatch (TV dominance). Second, the spatial mismatch mechanism follows a “weakened natural foundation with dual drivers of socio-economic dynamics and cultural policy momentum”, where the GDP, tertiary industry ratio, general public budget expenditure, number of ICH inheritors, museums, and key cultural relic protection units emerge as dominant factors. Third, core drivers demonstrate significant spatial heterogeneity, with economic factors showing differentiated regulation while cultural policy elements exhibit distinct regional dependency. The proposed “economy–culture” dual governance approach, featuring cross-scale analysis methods and three-dimensional indicator system innovation, holds practical value for optimizing cultural heritage spatial governance paradigms.